A study on utilization of antenatal care services in urban slums of Amritsar city, Punjab, India - Sharma, Nidhi; H. V., Kiran Kumar; Devgan, Shivesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Rapid urbanization in India is fuelling a growth in urban poverty, particularly in the urban slums where the quality of life is extremely poor. There have been limited efforts to capture the health of population living in urban slums and most severely affected are the women of childbearing age and children. So the present study was carried out to assess the utilization pattern of antenatal care and to identify the factors affecting it in urban slums of Amritsar city. Methods: A cross-sectional study was conducted in 1600 houses selected randomly in four slum areas of Amritsar city in which 659 married women in the reproductive age group of 15-49 years who had at least 1 child and had delivered the last child in the last 3 years were found. Total 659 women were interviewed using a pre-designed and pre-tested proforma. Results: 58.4% of respondent women attended at least one antenatal visit during last pregnancy. Maximum (43.4%) attended 2 antenatal visits. Majority (64.4%) had their first antenatal visit in 2nd trimester. Majority (57.1%) consumed <100 IFA tablets. Majority (65.6%) were fully immunized with 2 doses/booster of TT. Lack of knowledge about ANC services was the reason given by most of the women (31.0%) for not attending any antenatal visit. The utilization of antenatal care (ANC) services by women was found to be significantly associated with their age, education, birth order, socio-economic status and husband’s education. Conclusions: The utilization of antenatal care services was found to be poor in the study population. Important barriers to service utilization were found to be lack of awareness and lack of felt need. This shows the need for intensive efforts to be made in slum areas to create awareness among women by Behaviour Change Communication (BCC) activities.